Graphene‐Based Composites for Cancer and Antimicrobial Applications: From Structural Design to Clinical Practice - Jing Xu; Yujia Han; Haixiang Zeng; Hongxia Li; Xiaohui Niu; Xiaoyu Liu; Li Chen; Deyi Zhang; Dongqiang Zhang; Kunjie Wang (The Chemical Record, 2026)
Through synergistic interactions with functional components such as metals, metal oxides, polymers, and biomolecules, graphene‐based composites can simultaneously exhibit properties including photothermal conversion, drug delivery, imaging, and molecular recognition, demonstrating significant application potential in cancer diagnosis and treatment as well as antimicrobial therapy. Given that existing research has primarily focused on graphene materials themselves and that a systematic summary of the relationship between the preparation, structure, properties, and safety of graphene‐based composites is still lacking, this paper reviews preparation methods such as laser etching, hydrothermal synthesis, chemical vapor deposition, thermal reduction, water‐induced plastic foaming, and electrochemical exfoliation and analyzes their effects on material yield, particle size distribution, defect density, cost, and batch‐to‐batch consistency. It further outlines research progress in the field of tumor therapy, covering drug delivery, combination therapy, biosensing and diagnostics, toxicology, and antimicrobial applications. Particular attention is given to recent advancements in graphene‐based composites. Finally, the paper discusses the major obstacles to the clinical translation of graphene‐based composites, as well as the lack of standardized characterization and biosafety evaluation systems suitable for composite systems. In the future, a corresponding standardized evaluation framework should be established to lay the foundation for their safe, reproducible, and scalable biomedical applications.